Bird attacks on a butterfly with marginal eyespots and the role of prey concealment against the background. (2nd April 2013) - Olofsson, Martin; Jakobsson, Sven; Wiklund, Christer
<x xml:space="preserve">Abstract</x> Small eyespots on butterflies have long been thought to deflect attacks, and birds are the presumptive drivers selecting for these patterns; however, evidence of this function is still ambiguous. Marginal eyespots typically consist of a UV‐reflective white pupil, surrounded by one black and one yellowish ring. We have recently shown that Cyanistes caeruleus (blue tits) attack such eyespots, but only under low light intensities with accentuated UV levels: the increased salience of the eyespots relative to the rest of the butterfly probably explains this result. Possibly the background against which the butterfly is concealed may deceive birds to make similar errors. We therefore presented speckled wood butterflies decorated with eyespots (or controls without eyespots) to C. caeruleus against two backgrounds: oak and birch bark. Our results show that: (1) eyespots, independent of background, were effective in deflecting attacks; (2) the time elapsed between a bird landing and the attack was interactively dependent on the background and whether the butterfly bore an eyespot; and (3) the speed at which a butterfly was attacked predicted the outcome, with faster birds being more prone to errors than slower birds. This underscores a speed–accuracy trade‐off in the predators, and that background plays a role in the defensive qualities of marginal eyespots. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 290–297.